2016
DOI: 10.1093/jac/dkv493
|View full text |Cite
|
Sign up to set email alerts
|

A chemical susceptibility profile of thePlasmodium falciparumtransmission stages by complementary cell-based gametocyte assays

Abstract: This work indicates that the luciferase and gametocyte LDH assays are interchangeable and that their specific advantages can be exploited to design an HTS pipeline leading to new transmission-blocking compounds. Results from these assays consistently defined a gametocyte chemical susceptibility profile, relevant to the planning of future drug discovery strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Their results, which were based on % inhibition only and thus did not allow to compare threshold effects or potency, indicated that the compounds tested had a lower activity in the pLDH and ATP assays in comparison to the luciferase and resazurin assays. The second report, by D’Alessandro et al ., compared recently established luciferase and pLDH assays against early and late stage gametocytes in dose-response at a fixed incubation time of 72 h25. This study showed an excellent agreement between the two assays, which measure different biomarkers.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Their results, which were based on % inhibition only and thus did not allow to compare threshold effects or potency, indicated that the compounds tested had a lower activity in the pLDH and ATP assays in comparison to the luciferase and resazurin assays. The second report, by D’Alessandro et al ., compared recently established luciferase and pLDH assays against early and late stage gametocytes in dose-response at a fixed incubation time of 72 h25. This study showed an excellent agreement between the two assays, which measure different biomarkers.…”
Section: Discussionmentioning
confidence: 75%
“…These include the use of the metabolic indicator AlamarBlue18, parasite lactate dehydrogenase (pLDH)19, ATP production2021, expression of reporter genes in transgenic parasites lines22232425, fluorescent staining of gametocytes26, fluorescent staining of female gametes27, detection of female gamete specific antigens282930 and time-course imaging of exflagellating male gametocytes28.…”
mentioning
confidence: 99%
“…Dose-response curves on parasites exposed to MB for 24, 48 and 72h were readily obtained with an excellent assay Z′ factor (Zhang et al , 1999) of 0.88, confirming the potency of MB in killing mature gametocytes and showing that this increased with the time of drug exposure (Fig 3B). Importantly, the assay was able to detect MB gametocytocidal activity after only 24h of drug exposure, which is rarely observed in cell-based assays on stage V gametocytes even after treatment with potent gametocytocidal compounds such as epoxomicin (D’Alessandro et al , 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Assays to measure the killing of metabolically hypo-active gametocytes are challenging but different groups have developed several platforms (e.g. [14,19,20,23,27,31,34,[36][37][38][39][40]). In A primary screen is performed using an assay platform (e.g.…”
Section: Tier 1: Hit Identification and Validationmentioning
confidence: 99%
“…In A primary screen is performed using an assay platform (e.g. colorimetric [19,37], enzymatic, based on stage-specific reporters [36,38] or high-content imaging [20,23]), which is amenable to (medium-)/high-throughput screening (MTS/HTS). To date, no difference has been seen in activity of compounds tested against wild-type or transgenic parasite lines [36] although different genetic backgrounds should always be taken into consideration in the interpretation of results.…”
Section: Tier 1: Hit Identification and Validationmentioning
confidence: 99%